Surviving the Bible : a Devotional for the Church Year 2018 - Piatt, Christian (Surviving the Bible., 2018)
A lot of us have tried to read the Bible. And we've failed. Christian Piatt has too. But now, using the annual lectionary as his guide, he has put together a devotional that allows us to read through major parts of the Old and New Testaments and finally understand them in plain English. Every week has several Scripture readings, explanations of confusing terms, a story, a deeper dive into interesting themes, and a closing prayer. You can use it as a weekly study or browse a thematic list for something you're curious about. It's an ideal resource to use with a friend or small group, but it's set up to be accessed by anyone who has enough curiosity, openness, and desire to grow. Start anywhere. Set it down and come back to it. There's no "wrong way" to use Surviving the Bible. Engage ancient texts in new ways that make sense, here and now, maybe for the first time. Any way you use it, it's sure to challenge and inspire.